Labor and the Business Cycle: Some Industrial Aspects - Berridge, W. A. (The Review of Economics and Statistics, 1926)
A LTHOUGH there is still much that we do not know with even approximate accuracy regarding the inter-relations between labor and the business cycle, some definite advances have been made during the past few years.' The purpose of this article is to summarize and interpret the results of a few investigations in this field. Special consideration is given to their emphasis is given to the three topics, (I) employment, (2) labor mobility or turnover, and (3) operations of public employment offices. Of secondary importance, though very useful in interpreting the relations between labor and the business cycle, are (4) employment advertising in newspapers, (5) labor disputes, and (6) immigration.